Arthritis or an Adjacent Fascial Response? A Case Report of Combined Pyomyositis and Aseptic Arthritis - Noa Martonovich; Sharon Reisfeld; Yaniv Yonai; Eyal Behrbalk (Case Reports in Rheumatology)
Pyomyositis, accompanied by aseptic arthritis, has been previously documented in several publications. However, none of the authors in the mentioned case reports offered a pathophysiological explanation for this unusual phenomenon or proposed a treatment protocol. We present a case of a healthy, 70-year-old male who was presented to the emergency department 4 days after tripping over a pile of wooden planks and getting stabbed by a nail to his thigh. The right thigh was swollen. Unproportional pain was produced by a light touch to the thigh. A laboratory test and a CT scan were obtained. The working diagnosis was pyomyositis of the thigh and septic arthritis of the ipsilateral knee. The patient underwent urgent debridement and irrigation of his right thigh. An arthroscopic knee lavage was performed as well. Intraoperative cultures from the thigh revealed the growth of Streptococcus pyogenes and Staphylococcus aureus. Cultures from synovial fluid were sterile; thus, septic arthritis was very unlikely. The source of the knee effusion might have been an aseptic inflammatory response due to the proximity of the thigh infection. Anatomically, the quadriceps muscle inserts on the patella, and its tendon fuses with the knee capsule, creating a direct fascial track from the thigh to the knee. The inflammatory response surrounding the infection may have followed this track, creating a domino effect, affecting adjacent capillaries within the joint capsule, and causing plasma leakage into the synovial space, leading to joint effusion. Our suggested treatment is addressing the primary infection with antibiotics and considering adding anti-inflammatory therapy, given our suspicion that this process has an inflammatory component.